Pengaruh Kinerja ESG terhadap Nilai Perusahaan: Analisis Komparatif Sektor Barang Konsumen Primer dan Sekunder di Bursa Efek Indonesia 2021-2023 - Nadia Alifya Zahra; Ambar Kusumaningsih (Jurnal Riset Ekonomi dan Akuntansi, 2026)
This study examines the effect of Environmental, Social, and Governance (ESG) performance on firm value in the Consumer Staples and Consumer Discretionary sectors listed on the Indonesia Stock Exchange during 2021–2023. The study is motivated by inconsistent empirical findings regarding the relationship between ESG and firm value, as well as differences in sectoral characteristics that may influence ESG effectiveness. The objective of this study is to analyze the impact of ESG on firm value in both sectors and compare the differences between them. This research employs panel data analysis using samples of 23 Consumer Staples companies and 19 Consumer Discretionary companies over a three-year period, resulting in 69 and 57 observations respectively. The Fixed Effect Model was applied to the Consumer Staples sector based on the Hausman test result, while the Consumer Discretionary sector used the Random Effect Model. Firm value was measured using Tobin’s Q, ESG performance was proxied by Bloomberg ESG Score. The findings indicate that ESG has no significant effect on firm value in the Consumer Staples sector, while ESG has a significant negative effect in the Consumer Discretionary sector. These results suggest that the relevance of ESG depends on sector characteristics and market perceptions of ESG investment in Indonesia.